2017
DOI: 10.1007/s00018-017-2462-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the H+-ATP synthase by IF1: a role in mitohormesis

Abstract: The mitochondrial H+-ATP synthase is a primary hub of cellular homeostasis by providing the energy required to sustain cellular activity and regulating the production of signaling molecules that reprogram nuclear activity needed for adaption to changing cues. Herein, we summarize findings regarding the regulation of the activity of the H+-ATP synthase by its physiological inhibitor, the ATPase inhibitory factor 1 (IF1) and their functional role in cellular homeostasis. First, we outline the structure and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 157 publications
2
58
0
Order By: Relevance
“…The depletion of respiratory substrates, as observed in larvae cultured on low‐nutrient medium, should logically lead to the opposite outcome, that is, to the respiratory‐chain electron carriers becoming completely oxidized. However, respiratory chain shutdown might occur under such circumstances via the complex V inhibitor IF1 (Esparza‐Moltó, Nuevo‐Tapioles, & Cuezva, ), creating the conditions for AOX activation. AOX activation could, in principle, result from a number of metabolic consequences of low‐nutrient diet that are hard to predict, given that rather little is known about the nutrients (other than triglycerides) that are stored in the pupa.…”
Section: Discussionmentioning
confidence: 99%
“…The depletion of respiratory substrates, as observed in larvae cultured on low‐nutrient medium, should logically lead to the opposite outcome, that is, to the respiratory‐chain electron carriers becoming completely oxidized. However, respiratory chain shutdown might occur under such circumstances via the complex V inhibitor IF1 (Esparza‐Moltó, Nuevo‐Tapioles, & Cuezva, ), creating the conditions for AOX activation. AOX activation could, in principle, result from a number of metabolic consequences of low‐nutrient diet that are hard to predict, given that rather little is known about the nutrients (other than triglycerides) that are stored in the pupa.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that obese and T2DM patients present an increased activity of inhibitory factor 1 (IF‐1) in the mitochondrial matrix (Formentini et al., ). Inhibitory factor 1 is known to reduce the activity of ATP synthases, leading to a higher Δ p and electron leakage (Esparza‐Moltó, Nuevo‐Tapioles, & Cuezva, ). Therefore, other mechanisms might be playing important roles and affecting the results obtained here.…”
Section: Discussionmentioning
confidence: 99%
“…IF1 is consistently found to be dephosphorylated in hypoxic cells (6). Moreover, IF1 is highly overexpressed in cancer cell lines (8) and in prevalent human carcinomas (3,9), where it is found largely in its active dephosphorylated state (6). Because of the IF1-mediated inhibition of the ATP synthetic activity of the enzyme (6,8), the overexpression of IF1 in human carcinomas (3,9) and mesenchymal stem cells (10) has been shown to play a relevant role in triggering the metabolic reprogramming of the cells to an enhanced glycolytic flux.…”
mentioning
confidence: 99%
“…The inhibitor protein is encoded in the ATP5IF1 gene, which is located in chromosomes 1 and 4 in the human and mouse genomes, respectively. IF1 is a small, intrinsically disordered protein (2,3) that reversibly binds to the enzyme (4), inhibiting its ATP synthetic and hydrolytic activities, depending on cellular conditions (1,5). Phosphorylation of conserved S39 in human IF1 prevents its binding to the enzyme, and thus blocks its activity as an inhibitor of ATP synthase (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation